Pengaruh Rebusan Daun Mint Dan Rebusan Jahe Untuk Menghilangkan Mual Muntah Pada Ibu Hamil Trimester 1 Di Puskesmas Tanjung Agung - Jusmawati; Meilyta , Dewi (Jurnal Keperawatan Muhammadiyah, 2024)
The World Health Organization states that 14 percent of pregnant women experience vomiting and nausea during pregnancy. In the first trimester of pregnancy, around 73.5 percent of pregnant women in the United States, Australia and five European countries reported experiencing morning sickness. In Indonesia, 50 to 75 percent to 85% of pregnant women report experiencing nausea (Eka, 2023). During the first trimester of pregnancy, nausea and vomiting, known as emesis gravidarum, are very common. Although nausea and vomiting are more common in the morning, a condition called "morning sickness" can still occur at any time of the day or night. The aim is to determine the effectiveness of giving ginger tea and mint leaves for nausea and vomiting in pregnant women in the first trimester. This type of research is quasi experimental design research. The design used is a one group pre-posttest research design. The population in the study were all 1st trimester pregnant women who experienced nausea and vomiting at the Tanjung Agung Community Health Center in November-December 2023, a total of 80 1st trimester pregnant women. The results of the research were obtained using the Wilcoxon test analysis, namely a significance value of 0.00 (p<0.05), it can be concluded that there is a significant difference, the effect between boiled mint leaves on the intensity of nausea, and boiled ginger on the intensity of nausea with Wilcoxon test analysis, namely a significance value of 0.00. (p<0.05), it can be concluded that there is a significant difference in the effect of boiled ginger on the intensity of nausea